Dickson curves - Javier Gomez-Calderon (International Journal of Mathematics and Mathematical Sciences)
Let kq denote the finite field of order q and odd characteristic p. For a∈kq, let gd(x,a) denote the Dickson polynomial of degree d defined by gd(x,a)=∑i=0[d/2]d/(d−i)(d−ii)(−a)ixd−2i. Let f(x) denote a monic polynomial with coefficients in kq. Assume that f2(x)−4